Genetic variation in an international provenance-progeny test of Pinus caribaea Mor. var. bahamensis Bar. et Gol., in São Paulo, Brazil - Sebbenn, A. M.; Arantes, F. C. [UNESP]; Boas, O. V.; Freitas, M. L.M. (My University, 2008)
A combined provenance-progeny test of Pinus caribaea var. bahamensis was established in Paraguaçu Paulista Experimental Station, São Paulo State, Brazil, in a compact family blocks design with 14 provenances, 2 to 10 families per provenance, 5 individuals per subplot, and 7 replications. Variation among and within island, provenances and families and genetic parameters for d.b.h., height, and real volume were investigated, about 15 years after planting. Analysis of variation for all studied traits revealed significant differences among islands, provenances within island and families within islands, suggesting the possibility of increasing the timber yield through selection of the more productive provenances and families within the best island. Genetic correlations on growth traits were high and statistically significant, indicating that substantial gains could be made through indirect selection for one trait based on direct selection for another. Norman Castle provenance from Abaco Island performed best for d.b.h. height and volume, while San Andros and Little Harbour Cay, both from Andros Island performed worst for d.b.h. and height, respectively, and South Riding from Grand Bahamas Island performed worst for volume. The best provenance growth compared to that P. elliottii var. elliottii species at the same experimental site suggests that P. caribaea var. bahamensis has high silvicultural potential for the Paraguaçu Paulista region.
Keywords: Genetic parameters; Genetic variation; Pinus caribaea; Provenance-progeny test; Quantitative traits